2021
DOI: 10.1097/inf.0000000000003087
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Group A Streptococcus Infection in Children in Central Israel in 2012–2019

Abstract: Background: Group A Streptococcus can cause serious and sometimes life-threatening disease in children. The past few years have witnessed a rise in invasive group A Streptococcus infection (iGASi) for unclear reasons. This study attempted to describe the epidemiology, the clinical and demographic characteristics and the outcomes associated with iGASi in hospitalized children in central Israel Methods: We retrospectively analyzed the medical records of children <18 years old discharged with a diagnosis of iGASi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
2
2
0
4
Order By: Relevance
“…The most frequent types in children continued to be emm 1 and emm 12, both in our series and in that of other countries ( 26 ), as well as in many pre-pandemic pediatric cohorts ( 30 ). In our study, emm 89 lacking the has ABC locus was one of the most frequent types observed in mild cases; this emm type, which belongs to clade 3 and emerged in 2008 ( 31 ), has been described as associated with dermal infections ( 4 , 32 ).…”
Section: Discussionsupporting
confidence: 68%
“…The most frequent types in children continued to be emm 1 and emm 12, both in our series and in that of other countries ( 26 ), as well as in many pre-pandemic pediatric cohorts ( 30 ). In our study, emm 89 lacking the has ABC locus was one of the most frequent types observed in mild cases; this emm type, which belongs to clade 3 and emerged in 2008 ( 31 ), has been described as associated with dermal infections ( 4 , 32 ).…”
Section: Discussionsupporting
confidence: 68%
“…La susceptibilidad de los lactantes sin enfermedades previas, de presentar tanto EI como sus formas graves, ha sido referida previamente e implica que probablemente la inmunidad del hospedero está involucrada en su fisiopatología 4,13,27 . En esta comunicación los casos clínicos graves se presentaron, en su mayoría, en pacientes bajo 2 años de edad, con una media de edad más baja en relación con las formas menos graves.…”
Section: Discussionunclassified
“…En esta comunicación, el caso fatal sucedió en esta estación. Aunque no están definidos con claridad los mecanismos implicados, se plantea que ciertas proteínas del virus influenza, como la hemaglutinina podrían aumentar la virulencia del microorganismo y/o suprimir la respuesta inmune del hospedero 13,[29][30][31] . Son necesarias futuras investigaciones rigurosas desde el punto de vista metodológico para tratar de definir si la prevención de la infección por influenza podría reducir la EI por S. pyogenes.…”
Section: Discussionunclassified
See 2 more Smart Citations